Effect of Employee Competence and Internal Control Systems on Accounting Information Quality of the local Government in West Java region - Afiah, Nunuy Nur; Alfian, Adhi; Poppy, Sofia (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The purpose of this study was to empirically examine the effect of employee competence and internal control system on accounting information quality. The research was conducted to all local governments in the West Java region. The respondent are SKPD, PPKD, and the Regional Inspectorate on Local Government respectively; each local government sent six research questionnaires. The data analysis tool used was structural equation modeling (SEM). The results also show that employee competence and internal control system simultaneously gave the significant effect on accounting information quality, therefore a combination of both aspects can be considered as an improvement.